(untitled) (Environment & Health, 2017)
Objective: We determined the specific features of the biological action of chloroform and monochloroacetic acid with drinking water on the organism of the experimental animals according to the biochemical parameters. Materials and methods: A 6-month sanitary-and-toxicological experiment was performed using 10 groups of white, mongrel rats: 1 – control (they were given artesian water), 6 experimental groups drank water with chloroform, monochloroacetic acid, and their combination at levels 3 and 5 MPC, respectively, and 3 experimental groups that consumed drinking water with a standard content of both isolated substances and their combinations. The functional state of the animal body was assessed by the change in creatinine content, aminotransferase and alkaline phosphatase activity in serum and blood plasma. Results: Drinking water with the content of chloroform (CF) and monochloroacetic acid (MCAA) at the level of 1 MPC of both individual substances and their combination did not cause significant changes in the biochemical indices of the experimental animals. The dose-time dependence of changes in biochemical indices was revealed especially in the groups of animals drinking water with CF content at the level of 3 and 5 MPC and a combination of CF and MCAA (3 and 5 MPC). When drinking water is used with a combination of CF and MCAA the changes in biochemical parameters take place primarily due to the toxic effect of chloroform. The toxic effect of CF and MCAA in the excess concentrations causes changes in metabolic processes in the organism of animals, is manifested by the significant changes in the biochemical parameters of the blood, and, with an increase in the exposure time, can lead to the emergence of pathological processes in organs sensitive to the action of organochlorine compound (liver, kidney, heart).